Perbaikan Status Gizi Stunting Dengan Pemberian Modifikasi Formula Ikan Haruan Dan Formula Ayam Di Wilayah Kerja Puskesmas Martapura Timur Kabupaten Banjar, Kalimantan Selatan - Magdalena; Fathurrahman (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Stunting is one of the nutritional problems caused by malnutrition and is related to insufficient nutrition in the past, resulting in the occurrence stunting included in a problem chronic malnutrition. Prevalence of toddlers stunting According to districts/cities, the results of the 2021 Indonesian Nutrition Status Study (SSGI) showed that South Kalimantan Province was in 6th place with a percentage of 30.0%. Banjar Regency is still continuing its efforts to reduce the prevalence of stunting. According to data from the Banjar District Health Service in March 2023 at the East Martapura Community Health Center, there were 188 stunted toddlers. In the Central Malay village, 16 children under five were stunted. The aim of this activity is to improve the nutritional status of stunting in the work area of ​​the East Martapura Community Health Center, Banjar Regency, South Kalimantan Province. Community service activities include education about stunting, practice in making haruan fish formula and chicken formula and assistance in giving formula for six days to stunted toddlers. The results of this activity: the knowledge of mothers of stunted toddlers and cadres has increased. The practice of making haruan fish formula and chicken formula has been carried out as well as mentoring and giving formula to stunting toddlers for six days. The achievements obtained were: 9 toddlers whose weight (BB) increased (81.82%), 2 toddlers whose weight remained the same (18.18). Toddlers' height (TB) increased by 4 toddlers (36.36%) and their height remained 7 toddlers (63.64%).